Extensive Listening in Controlled Classroom Practice: Exploring its Benefits for EFL Learners - Nurhayati, Ganinda; Rini, Lindawati (EDUCAFL: Journal on Education of English as Foreign Language, 2025)
This study investigates the implementation and perceived benefits of extensive listening as a controlled classroom activity in an English as a Foreign Language (EFL) context. While extensive listening is often promoted as an autonomous learning activity that enhances listening fluency and motivation, its integration into formal classroom settings remains limited and underexplored. Using a qualitative case study approach, this research was conducted over six weeks with one EFL lecturer and 25 intermediate-level university students. Data were collected through classroom observations, semi-structured interviews, and document analysis of lesson plans and student reflection logs, and analysed thematically. Findings indicate that when extensive listening is delivered in a structured format it fosters high levels of learner engagement, increases listening comprehension, and boosts student confidence. Students appreciated the combination of teacher guidance and personal autonomy, as it allowed them to engage meaningfully with relevant and emotionally resonant content while receiving consistent feedback. The study highlights the value of balancing structure and freedom in classroom-based listening pedagogy and offers a practical model for integrating extensive listening into EFL instruction. These results contribute to the growing literature on listening pedagogy by addressing how controlled extensive listening can be feasible and impactful in formal education contexts.